Pengembangan Media Pembelajaran Al-Qurâ€™an dan Hadist Untuk Anak Usia Dini Melalui Game Interaktif â€œAbatasaâ€ di Masa Pandemi Covid- 19 - Munawaroh, Hidayatu; Widiyani, Afifah Eka Yulia; Chasanah, Nikmatul; Fauziddin, Mohammad (Khalifa Journal of Islamic Education, 2022)
The study aims to design and analyze the effects of multimedia use on the Quran study for young children. Research takes place through two stages. First, using the method of Research and Development (R & D) to design the media to be used. Second: A quantitative method with a type of correlation to see how the use of media to learners in the study of the Koran will affect them. To produce properly functional and operational media products, the author tests the validity of two experts in each field. Next, to note the effects of the media use produced, observation was made during the learning process in the class and on the test sheets of the learner's work. Research shows that, first, the resulting media can function and operate properly as a Koran learning medium. Second, the resulting multimedia use has affected learners' learning, which is shown by the increased value of post-test participants to 2.73 from a previously pre-test score of 2.07. Even the sharpness of the learning result reached 80%, indicative of a significant increase of 0.66. Referring to the results of this study, the multimedia produced could be used as one of the alternatives for teachers in the Quran study for young children.